APLIKASI FILTER DIGITAL FIR DAN IIR UNTUK MENGHILANGKAN NOISE PADA SINYAL SUARA - Muhammad Syahroni; Muhammad Nasir (Politeknik Negeri Lhokseumawe, 2014)
In the transmission process of signal from the transmitter to the receiver, the noise will be induced to the signal which will deteriorate the overall quality of the information signal in the receiver. To improve the signal to noise ratio, hence the noise must be suppressed. In this paper, digital filter will be implemented to reduce the noise by using Finite Impulse Response (FIR) and Infinite Impulse Response (IIR) methods. The input signal will be fed to FIR or IIR filter, and the filter algorithm will be designed according to the different filter order. The noise level at filter output will be examined according to different filter order for each FIR and IIR. The simulation result shows that IIR filter is better than FIR filter in reducing the noise. The best result for IIR filter is for filter order of 12 which suppressed the noise to -92 dB, compared to FIR filter which only reduced the noise to -40 dB